Symbol Error Rate Analysis of M-QAM with Equal Gain Combining Over A Mobile Satellite Channel - Zachaeus Kayode Adeyemo; Isaac A. Ojedokun; Damilare O. Akande (International Journal of Electrical and Computer Engineering (IJECE), 2013)
Mobile Satellite Communications (MSC) have become an essential part of the world telecommunication infrastructure. However, the systems suffer from multipath propagation effects. In this paper, error analysis of M-ary quadrature amplitude modulation (M-QAM) with Equal Gain Combiner (EGC) over mobile satellite channel was carried out. The satellite channel was modelled as the product of Rayleigh and Ricians. This was then used to develop a system model for the received signal which was simulated and evaluated in terms of Average Symbol Error Rate (ASER) using the exact closed-form expression derived from moment generating function (MGF) and Padé Approximants (PA) theory. The results showed that at 16dB, Rician factor ‘k’=0, ASER obtained are 41.83%, 18.56% and 10.81% for paths ‘L’ = 2, 3, 4 respectively. ASER values reduced as ‘k’ increased. The results are in agreement with the simulation.DOI:http://dx.doi.org/10.11591/ijece.v3i6.4343